The importance of lag screw position for the stabilization of trochanteric fractures with a sliding hip screw: A subject‐specific finite element study1. Issue 4 (8th November 2012) - Goffin, Jérôme M.; Pankaj, Pankaj; Simpson, A. Hamish
Abstract Using finite element analysis, we compared the biomechanical performance of a CT scan‐based three‐part trochanteric fracture model (31‐A2 in the AO classification) stabilized with a sliding hip screw for nine different positions of the lag screw (3 × 3 arrangement, from anterior to posterior and from inferior to superior). Our results showed that the volume of bone susceptible to yielding in the head and neck region is the lowest for inferior positions and increases as the lag screw is moved superiorly. Overall, for this specific subject, the models less likely to lead to cut‐out are the ones corresponding to inferior middle and inferior posterior positions of the lag screw. In our study, the tip‐apex distance (TAD) was anti‐correlated with the risk of cut‐out, as quantified by the volume of bone susceptible to yielding, which suggests that a TAD >25 mm cannot be considered to be an accurate predictor of lag screw cut‐out. Further clinical studies investigating lag screw cut‐out should attempt to find more reliable predictors of cut‐out that should better reflect the biomechanics and subject‐specificity of the femoral head. © 2012 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31: 596–600, 2013